PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Teti Ratnawulan; Ricky Yoseptry; Iis Kusmiati; Lilis Widiawati; Nenden Noer Kusmawati (STKIP PGRI Situbondo, 2024)
The background of this research is based on the need to understand the influence and implications of utilizing Information and Communication Technology (ICT) in the learning processes of 10th-grade students at SMAN 1 Banjaran. The implementation of technology in the educational context has become an integral part of enhancing learning quality and influencing students' motivation to learn. A qualitative method was employed. Data were gathered in the field through in-depth, structured interviews, and from literature sources. Findings from the literature review and field study are presented as research outcomes. The presented data are then abstracted with the objective of showcasing facts. In the subsequent stage, this data is interpreted to produce information or knowledge. The study concludes that the use of ICT at SMAN 1 Banjaran, especially by 10th-grade students, has a significant impact on the learning context. Although the majority of students actively use the internet for learning, challenges such as unstable connections and inadequate devices remain barriers. The majority of students show good learning motivation, but there is a small group that is less motivated, emphasizing the importance of a more inclusive learning approach. Nonetheless, the use of technology contributes positively to student engagement. Despite challenges such as access difficulties and technological limitations, more effective utilization of ICT is expected to enhance the overall learning motivation of students at SMAN 1 Banjaran